Diurnal time budgets of American Green-winged Teal Anas crecca breeding in British Columbia - Paquette, Gil A; Ankney, C Davidson (Wildfowl, 1998)
American Green-winged Teal are the smallest North American Anas. Because of their small size and early nesting chronology, females may have little ability to use nutrient reserves for egg production or to meet subsequent costs of incubation. Thus, they probably rely heavily on exogenous resources for reproduction. From 21 April to 17 June 1993, we determined diurnal time budgets of breeding Green-winged Teal by observing 12 pairs for 26.4 and 52.0 hours during pre-rapid follicular growth (pre-RFG) and rapid follicular growth (RFG), respectively, and 10 pairs for 20.1 hours during incubation. Females spent more time foraging during RFG (74%) than during pre-RFG (35%). Males spent similar time foraging during pre-RFG and RFG (30% and 35%, respectively). Female Green-winged Teal spent more time foraging during incubation breaks than males and as much or more time foraging than females of other Anas species during RFG and incubation breaks. Time budgets of female Green-winged Teal indicate a strong reliance on breeding area resources for reproduction.